Arctic Geopolitics, Media and Power - Nilsson, Annika E. (Routledge Geopolitics Series, 2019)
Arctic Geopolitics, Media and Power provides a fresh way of looking at the potential and limitations of regional international governance in the Arctic region. Far-reaching impacts of climate change, its wealth of resources and potential for new commercial activities have placed the Arctic region into the political limelight. In an era of rapid environmental change, the Arctic provides a complex and challenging case of geopolitical interplay. Based on analyses of how actors from within and outside the Arctic region assert their interests and how such discourses travel in the media, this book scrutinizes the social and material contexts within which new imaginaries, spatial constructs and scalar preferences emerge. It places ground-breaking attention to shifting media landscapes as a critical component of the social, environmental and technological change. It also reflects on the fundamental dilemmas inherent in democratic decision making at a time when an urgent need for addressing climate change is challenged by conflicting interests and growing geopolitical tensions. This book will be of great interest to geography academics, media and communication studies and students focusing on policy, climate change and geopolitics, as well as policy-makers and NGOs working within the environmental sector or with the Arctic region.